Методика провединия комплексного анализа финансового состояния предприятия и разработка по повышению его платежеспособности - Басте, Т.У. (Культура народов Причерноморья, 2013)
Рассмотрены теоретические основы проведения комплексного анализа финансового
состояния предприятия; проведен анализ и дана оценка финансовому состоянию, результатам
деятельности. Проведен анализ управления платежеспособностью предприятия; разработан комплекс
мер направленных на повышение уровня платежеспособности предприятия. Комплексность
выражается во всестороннем финансовом анализе производственной, инвестиционной и финансовой
деятельности предприятия. В статье проводится анализ зарубежных и российских методик и
математических моделей комплексной диагностики финансового состояния предприятия.
Ключевые слова: финансовый анализ, платежеспособность, финансовая устойчивость, денежный
поток, финансовые результаты, эффективность финансовой деятельности. Розглянуто теоретичні основи проведення комплексного аналізу фінансового стану
підприємства; проведено аналіз і дана оцінка фінансового стану, результатів діяльності. Проведено
аналіз управління платоспроможністю підприємства; розроблено комплекс заходів, спрямованих на
підвищення рівня платоспроможності підприємства. Комплексність виражається у всебічному
фінансовому аналізі виробничої, інвестиційної і фінансової діяльності підприємства. У статті
проводиться аналіз зарубіжних і російських методик і математичних моделей комплексної діагностики
фінансового стану підприємства.
Ключовi слова: фінансовий аналіз, платоспроможність, фінансова стійкість, грошовий потік,
фінансові результати, ефективність фінансової діяльності. Theoretical the basics of carrying out complex financial analysis of the entity; the analysis is carried
out and the assessment is given to a financial condition, results of activities. The analysis of management is
carried out by solvency of the entity; the package of measures directed on increase of level of solvency of the
entity is developed. Complexity is expressed in a comprehensive financial analysis of productive, investing and financial activities of the entity. In article the analysis of foreign and Russian techniques and mathematical
models of complex diagnostics of a financial condition of the entity is carried out. The role and place of
depreciation policy in achievement of reproduction balance of the entity are discussed. In article the
management system is considered by receivables. In article the attention to the mandatory requirement to
observe compliance between type of cash flows or profits and a cost rate on the equity is paid. This article
considers algorithm of interaction of participants of production process. As the economic essence of the complex
analysis, its types and benefits is considered, and also the analysis of modern techniques of its carrying out is
provided. The problems explaining need of carrying out the analysis aren't least described. In article the
overview of benefits of carrying out a financial analysis is carried out, and also the specific example of carrying
out the complex analysis of the entity is given. On the above example change of profitability and rationality of
carrying out the analysis is shown.
Key words: financial analysis, solvency, financial stability, cash flow, financial results, efficiency of financial
activities.